The role of deubiquitinases in cardiac disease - Xiaona Zhan; Yi Yang; Qing Li; Fan He (Expert Reviews in Molecular Medicine)
Deubiquitinases are a group of proteins that identify and digest monoubiquitin chains or polyubiquitin chains attached to substrate proteins, preventing the substrate protein from being degraded by the ubiquitin-proteasome system. Deubiquitinases regulate cellular autophagy, metabolism and oxidative stress by acting on different substrate proteins. Recent studies have revealed that deubiquitinases act as a critical regulator in various cardiac diseases, and control the onset and progression of cardiac disease through a board range of mechanism. This review summarizes the function of different deubiquitinases in cardiac disease, including cardiac hypertrophy, myocardial infarction and diabetes mellitus-related cardiac disease. Besides, this review briefly recapitulates the role of deubiquitinases modulators in cardiac disease, providing the potential therapeutic targets in the future.